Antigen-Independent IFN-γ Production by Human Naïve CD4+ T Cells Activated by IL-12 Plus IL-18 - Munk, Rachel B.; Sugiyama, Katsuki; Ghosh, Paritosh; Sasaki, Carl Y.; Rezanka, Louis; Banerjee, Kasturi; Takahashi, Hidenori; Sen, Ranjan; Longo, Dan L. (PloS one, 2011)
The role of T cells in innate immunity is not well defined. In this report, we show that a subset of human peripheral blood CD4(+) T cells responds to IL-12 plus IL-18, but not to IL-12 or IL-18 alone, by producing IFN-γ in the absence of any antigenic stimulation or cell proliferation. Intracellular staining reveals a small percentage of resting CD4(+) T cells (0.5 to 1.5%) capable of producing IFN-γ in response to IL-12 plus IL-18. Interestingly, both naïve (CD45RA(+)) and memory (CD45RO(+)) CD4(+) populations were responsive to IL-12 plus IL-18 stimulation in producing IFN-γ. The expression of IFN-γinduced by IL-12 and IL-18 is sensitive to rapamycin and SB203580, indicating the possible involvement of mTOR and p38 MAP kinase, respectively, in this synergistic pathway. While p38MAP kinase is involved in transcription, mTOR is involved in message stabilization. We have also shown that NFκB family member, cRel, but not GADD45β and GADD45γ, plays an important role in IL-12 plus IL-18-induced IFN-γ transcription. Thus, the present study suggests that naïve CD4(+) T cells may participate in innate immunity or amplify adaptive immune responses through cytokine-induced antigen-independent cytokine production.